EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH PIJAT EFFLEURAGE TERHADAP PENURUNAN NYERI PADA IBU BERSALIN KALA I - Ramadiyanti, Aliya (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background : Labor pain can cause stress or fear which can result in increased secretion of catecholamine and cortisol levels, resulting in decreased uterine blood flow and decreased uterine contractility which can affect the labor process. One of the non-pharmacological actions that can be taken to reduce labor comfort is by using a massage or stroking method on the stomach, namely effleurage massage. Effleurage massage is a light massage using the fingers, usually on the stomach, in rhythm with breathing during contractions. Purpose : To applied the effleurage massage on reducing labor pain in the first stage. Method : The method used is to search for evidence through databases from Google Scholar and the Garuda Portal published in 2016-2023. Results : There was a decrease in labor pain scores using the Numeric Rating Scale (NRS) after effleurage massage. Conclusions : The application of effleurage massage can be applied to maternal in the first stage of labor to reduce the intensity of labor pain.